Relationships between Sport, Work and Leisure-Time Physical Activity among Lithuanian University Students - Brigita Miežienė; Laimutis Šiupšinskas; Rasa Jankauskienė (Lithuanian Sports University, 2018)
Research background and hypothesis. Other than sport physical activity which occurs in occupational, leisure and domestic sectors is often overlooked, meanwhile it also affects health. Previous research revealed that energy expenditure in occupational, domestic and leisure-time domains may inﬂ uence energy expenditure in sports or exercising domain. University students are understudied population in this area. We expected that lower work and leisure-time activity among university students would be associated with their higher sports related activity. Research aim was to examine relationships between sport, work and leisure-time activities in a sample of university students. Research methods. The ﬁ nal sample consisted of 867 students from four Lithuanian universities, 195 (22.5%) were males, their age ranged from 18 to 22 years. Baecke Questionnaire of Habitual Activity (Baecke et al., 1982) was used to assess work, leisure-time and sport physical activity. Research results. Male students scored signiﬁ cantly higher than female in work and sport activity (p < 0.0001), but not in leisure-time activity (p = 0.61). Males and females who were more active in their occupational domain were also twice more active in sports-related activities (OR = 2.22 [95% CI 1.25-3.93] and OR = 2.14 [95% CI, 1.50-3.04] respectively). Females who were more active in leisure-time domain were almost twice more active in sports-related activities (OR  = 1.65 [95% CI 1.22-2.21]) as well.   Discussion and conclusions. Analysis of the relationships between sports, work and leisure-time physical activities did not conﬁ rm our expectation. The results of the current study revealed that lower physical activity in occupational or leisure-time domains did not determine higher sports related physical activity. Sports-related activity and physical activity in other domains can coexist together in the population of students and possibly depends on variables which inﬂ uence them all. In further research, the broader set of variables inﬂ uencing university students' habitual physical activity should be taken into account. Keywords: habitual physical activity, physical activity domains, occupation of university students.